Constitutive relationship of 4Cr9Si2 and technological parameters on the inner bore of cross wedge rolling for preform hollow valves. Issue 9 (October 2016) - Ji, Hongchao; Liu, Jinping; Wang, Baoyu; Tang, Xuefeng; Huo, Yuanming; Zhou, Jing; Hu, Zhenghuan
Abstract The hot deformation behavior of 4Cr9Si2 heat-resistant steel was investigated by hot deformation compression tests in the deformation temperature range of 950–1180 °C with strain rates of 0.1–10 s−1 . The constitutive equation of 4Cr9Si2 heat-resistant steel was established to describe the peak stress as a function of the deformation temperature and strain rate. The deformation characteristics of the cross wedge rolling (CWR) process of preform hollow valves are analyzed. By using DEFORM-3D software for finite element simulation tools, the process of CWR forming hollow valves was analyzed. According to the finite element simulation results, which reveal the influence of different process parameters on the inner diameter of the hollow valve blank, changing the stretching angle of the die design method effectively improves the position wedge reaming of the workpiece.